Pengaruh Demokrasi, Kekuatan Politik dan Ukuran Pemeritah Daerah terhadap Transparansi Keuangan Pemerintah Daerah - Suci Novalia; Deviani Deviani (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to analyze the influence of democracy, analyze the influence of political power and analyze the influence of local government measures on the financial transparency of regency/city governments in Jambi Province. The population in this study was the Regency/City Regional Government in Jambi Province with a total sample of 44 samples during 4 years of observation (2017-2020). The data analysis technique used in this study is panel data regression analysis. The result of this study is that democracy has a significant effect on the transparency of local governments in districts/cities throughout Jambi Province. The high level of democracy in the Jambi regional government affects the financial transparency of the regional government of Jambi Regency/City. The high level of democracy in the Jambi regional government affects the financial transparency of the regional government of Jambi Regency/City. The first hypothesis (H1) which states that local government transparency has a significant positive effect on the transparency of local governments in districts/cities throughout Jambi Province is accepted. Political ideology has no effect on the transparency of local governments in districts/cities throughout Jambi Province. The high and low number of parties winning legislative elections has no effect on the transparency of local governments. Political ideology does not affect the degree of disclosure of information and transparency. The second hypothesis (H2) which states that political power does not have a significant effect on the transparency of local governments in districts/cities throughout Jambi Province is not accepted The size of local governments has a significant positive effect on the transparency of local governments of districts/cities throughout Jambi Province. The larger the size of local government, the more transparency of local governments will also increase. The third hypothesis (H3) which states that the size of the government has a significant positive effect on the transparency of local governments in districts/cities throughout Jambi Province is accepted.